Costs of production of all year-round vs block calving herds in the UK - Ham, V.; Kliem, K.E.; Crompton, L.A.; Gadanakis, Yiorgos (My University, 2025)
The UK's climate and topography enables multiple different calving patterns to operate within the same market, facilitated by industry infrastructure that allows for a variety of milk purchasing arrangements. All year round (AYR) calving is most common, and with current labor challenges spring block (SB), autumn block (AB) and twin block (TB) calving systems could potentially become more popular, but research comparing the efficiency of AYR with block calving systems operating within the same market conditions is limited. This study compared the costs of production of AYR against 3 block calving systems on a pence per energy corrected milk liter (PPL), to assist benchmarking activities, costs and management decisions. Farm accounts data (from 2017 to 2020), from 604 farms broadly representing the national split of calving patterns in the UK, were included in a linear mixed effects (LME) model used for inference with maximum likelihood estimation. Random effects included year and farm, with fixed effects including herd size (cows), farm size (hectares) and average annual milk yield per cow that were each standardized to enable all calving patterns to be compared at the same scale (i.e., same herd size, farm size and milk yield). Calving pattern was self-determined by the farmer under guidance from a trained data collector. Cost of production variables investigated included milk price, stock sales (calves, cull cows, breeding animals), total income (all dairy farm revenues), total purchased feed, purchased forage, variable costs, gross margin, labor, overhead costs and net profit. Autumn block herds had lower total income, lower forage purchases, higher labor and lower net profit compared with AYR. Spring block herds had higher total income, higher forage purchases, lower labor and lower overhead costs compared with AYR. There were no differences between TB and AYR herds. Using the LME model, the impact of changing the fixed effects on costs of production were estimated, based on a 1 Standard Deviation (SD) change. Increasing herd size (1 SD, 345 cows) was associated with a reduction in net profit of AB herds by 3.34 PPL but an increase in net profit for SB herds by 5.57 PPL compared with AYR. Increasing farm size (1 SD, 164 ha), all 3 block calving herds had different associations compared with AYR; net profits would be increased for AB and TB herds (by 1.33 and 2.12 PPL, respectively) while SB herds would have reduced net profit by 4.26 PPL. Increasing energy corrected milk yield (1 SD, 4,038 L) would only benefit the net profit of SB herds over AYR by 6.04 PPL as SB herds had the lowest milk yield per cow. The results demonstrated that increasing land, cows or milk yield per cow was associated with different responses in cost of production depending on calving pattern. Findings from this study could be used by extension services, farm advisers and farmers for benchmarking purposes and when considering farm-scale decisions or switching from an AYR to block calving pattern.
Costs of production of all year-round vs block calving herds in the United Kingdom
Keywords: All year round calving; Seasonal calving; Costs of production; Linear mixed effects